Beam structure made of oil palm fibre-epoxy composite / Valliyappan David Natarajan, Mimi Azlina Abu Bakar and Anizah Kalam - Natarajan, Valliyappan David; Abu Bakar, Mimi Azlina; Kalam, Anizah (2006)
In those days, the construction of bridges mainly utilized components made of steel in the form of trusses, arches and beams. Nowadays, a large numbers of researchers and institutions have been working towards exploring the potential of such new materials and their adequate application to structural engineering design. The potential for the use of natural fibre reinforced composites for this application is enormous, which also contribute positively to waste management solutions in the oil palm mill or plantation. The objectives of this fundamental research project are to obtain basic mechanical properties of composite materials (bars) made of indigenous natural fibres sourced from oil palm tree namely the oil palm empty fruit bunch (OPEFB) fibre and oil palm frond (OPF) fibre mat and sugar cane husk (SC). The OPEFB samples consist 10 % and 20 % (mass fraction) of EFB fibres while the SC sample is made of 10 % of SC fibre. The tensile strength of composites made from OPEFB appreciates 35% as compared the homogeneous epoxy. Although the average flexural strength for both of the composites is less than the homogeneous epoxy, the flexural modulus of the OPEFB composite increased up to 62%. The presence of OPEFB fibre and OPF fibre mat improved the impact strength of the homogeneous epoxy as much as 40%. Based on these results, we have simulated the use of the composites, which we term semi-structural-members, namely the column and beam to build short span bridge (SSB) using LUSAS®. Results of the FEM analysis indicated that the 10% OPEFB composite would be able support about 200 kg load with a maximum deflection of 0.05 mm and 0.2 mm for the 5-m and 7-m span SSB, respectively using the T-beam configuration. This outcome, when compared to the strain at failure, indicates the potential use of OPEFB to build moderate load supporting structures but also in reducing the cost of SSB for usage in the rural areas as well as in recreational spots in the urban areas.